2021
DOI: 10.21003/ea.v193-16
|View full text |Cite
|
Sign up to set email alerts
|

The effects of accounting information system quality on financial performance

Abstract: Decision-making by management is supported by quality accounting information, which is produced by a quality accounting the current research is to determine empirically the impact of organizational framework on the accounting information systems quality and their effects on the financial status. In this study, we use structural equation modeling with the PLS approach to analyze 72 respondents who come from star hotels in the city of Bandung, West Java, Indonesia. The results show that the overall organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The findings indicate a significant positive association of system quality towards organizational effectiveness in the SMEs (manufacturing companies). This might be because the accounting information system is well designed and implemented, thus, leading to relevant, accurate, complete and timely information (Anggraeni & Winarningsih, 2021). The results are also consistent with Gorla et al (2010), that found significant positive influence of system quality towards acceptance of the system, leading to a positive impact on organizational effectiveness.…”
Section: Regression Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…The findings indicate a significant positive association of system quality towards organizational effectiveness in the SMEs (manufacturing companies). This might be because the accounting information system is well designed and implemented, thus, leading to relevant, accurate, complete and timely information (Anggraeni & Winarningsih, 2021). The results are also consistent with Gorla et al (2010), that found significant positive influence of system quality towards acceptance of the system, leading to a positive impact on organizational effectiveness.…”
Section: Regression Analysissupporting
confidence: 80%
“…Thus, the acceptance leads to an increase in the efficiency and effectiveness of organizational performance. Anggraeni and Winarningsih (2021) stated that quality of a well-designed accounting information system can produce quality accounting information. A good quality system that is better integrated, accessible, and flexible, tends to produce relevant, accurate, complete, and timely information.…”
Section: System Quality and Organizational Effectivenessmentioning
confidence: 99%